Біохімічний склад плодів актинідії - Skripchenko, N.V.; Kalaida, K.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
Results of study of biochemical content of actinidia’s fruit, grown in M.M. Grуshko National Botanical Gardens of the NAS of Ukraine and the dynamics of this content during the process of storage and processing of fruits are presented.